Advertisement call and description of the tadpole of Microhyla marmorata Bain & Nguyen, 2004 from Xuan Son national park, Phu Tho province - Dung, Le Trung; Hoa, Ninh Thi; Anh, Luong Mai; Truong, Nguyen Quang (Academia Journal of Biology, 2016)
Microhyla marmorata Bain & Nguyen, 2004 is recorded for the first time from Xuan Son National Park. Descriptions of the advertisement call and the tadpole of Microhyla marmorata are also provided. Calls consist multi-notes (2-4 notes/call), with dominant frequency at 2.756-3.015 kHz and are emitted from the water surface during the night. Morphorlogical characters of the tadpoles (Gosner stages 25-36 and 39, 40) are as the following: Size small, body yellowish brown with a dark grey blotch between eyes, extending forward to opening of spiracle; body wide ca. 1.2 of body hieght (BW/BH: 1.09-1.37), approximately 0.69 of body lenght (BW/BL: 0.61-0.78); oral disc absent; tail three times longer than high (TAL/HT 2.44-4.49).